Bone quantification. Issue 5 (October 2017) - Robertson, Alastair; Godavitarne, Charles; Peters, Jonathan
Abstract: Bone quantification has a number of roles within the healthcare environment. There are three current methods used for bone quantification in clinical use including dual-energy X-ray absorptiometry (DEXA) scanning, quantitative CT (QCT) and quantitative ultrasound (QUS). DEXA scanning is the most familiar modality used to assess bone mineralization. It is used to generate the World Health Organization standardized T-score as a measure of bone density. There are pros and cons to all three methods of bone quantification and it is important to consider these when choosing the appropriate modality to use and why, within specific patient groups, different methods can be more effective at bone quantification and identifying patients at risk of fragility fractures.